Interdisciplinary Arendt: Pluralism – Promise – Problems, University of Aberdeen, 22nd – 25th August 2023. (Maria Robaszkiewicz & Michael Brown) - Robaszkiewicz, Maria; Brown, Michael (HannahArendt.net, 2024)